Assessment Of Vascular And Lymphatic Vessels Density In Benign Vascular Lesions Using CD34 And D2-40 Immunohistochemical Markers - Tater, Jawaher M; Abdullah, Bashar H (Journal of Baghdad College of Dentistry, 2017)
Background: Vascular tumors and malformations, comprising a broad category of lesions often referred to as vascular anomalies. Hemangioma, represents a variety of vascular lesions (both malformations and tumor), while lobular capillary hemangioma is a common vascular lesion of the skin and mucous membranes that occurs mainly in children and young adults. Lymphangiomas are malformations of the lymphatic system. At the level of light microscopy the small lymphatics vessels may be similar to capillaries and sometimes are only tentatively identified by the nature of their contents or by immunohistochemical staining procedure. This study aimed to assess the vascular and lymphatic vessels density in benign vascular lesions using CD34 and D2-40 immunohistochemical markers. Materials and Methods: Twenty two formalin-fixed paraffin-embedded tissue blocks of Hemangioma/vascular malformation, thirty of lobular capillary hemangioma and another twenty of lymphangioma. Results: Lymphatic vessel density expressed by D2-40 immunomarker was found in all cases with mean (24.01±14.74) in lymphangioma ,for lobular capillary hemangioma it was (12.67±6.66) and for hemangioma was (9.77±6.82) where as the mean of microvessel density count measured by CD34 immunomarker was (49.87±31.97) for lobular capillary hemangioma , in hemangioma it was (37.42±23.40) and (25.90±12.23 ) for lymphangioma. Conclusions: All vascular lesions are a mixture of blood and lymphatic vessels with different proportions, hemangioma shows high percentage of blood vessels and lymphangioma shows high percentage of lymphatic vessels.